2006
DOI: 10.1007/s00266-005-6095-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of the External Ear in Our Adult Population

Abstract: This study aimed to determine the mean values of the different morphometric measurements from right and left ears. These measurements were taken from 341 healthy young adults (150 women and 191 men) ages 18 to 25 years using an electronic digital caliper. The results showed the mean values for total ear height, lobular height and width, distances from tragus to antihelix and to helix, and ear projection and width to be, respectively, 59.7 +/- 3 mm, 17.5 +/- 1.4 mm, 18.5 +/- 2.2 mm, 16.6 +/- 1.7 mm, 25.1 +/- 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
81
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 23 publications
10
81
0
11
Order By: Relevance
“…Sexual dimorphism is seen in the auricular linear dimensions with higher values in males. Brucker et al [5] observed an average LH to be 1.88cm and according to a study done by Bozkir et al [2] LH was 1.8 cm in young men and 1.7 cm in young women. Mc Kinney et al [15] obtained data from 100 volunteers and found a mean LH of 1.8 cm.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Sexual dimorphism is seen in the auricular linear dimensions with higher values in males. Brucker et al [5] observed an average LH to be 1.88cm and according to a study done by Bozkir et al [2] LH was 1.8 cm in young men and 1.7 cm in young women. Mc Kinney et al [15] obtained data from 100 volunteers and found a mean LH of 1.8 cm.…”
Section: Methodsmentioning
confidence: 92%
“…Its size ,shape and spatial location on the face are important from an esthetic point of view [1]. Earlobe occupies an unique position among the structures of the face and is a very important region in esthetic composition of the ear [2]. lery on this site.…”
Section: Introductionmentioning
confidence: 99%
“…Çıplak gözle kulak görüntüle-rinin bire bir karşılaştırması, şüpheli kişiler arasında suçun fail(ler)inin ayırt edilmesi için, polis memurları tarafından uy- [2,3] opposing to some authors' opinion: "The features of an ear are not expected to be very distinctive in establishing the identity of an individual" [4]. The shape of the ear gives information about age and sex, which is clear.…”
Section: Sonuçunclassified
“…It can be perceived easily that structures of auricle convey signs of age and sex although not easily defined. They are important for the maintainence of a harmonious and pleasing appearance of the face (Brucker et al, 2003;Bozkir et al, 2006). In an anthropometric growth study of external ear in Canadian Caucasians, it was found that the auricle width and auricle length reached the mature size in males at 7 and 13 years and in females at 6 and 12 years; respectively (Farkas et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…There were fine and detailed studies on morphometry of the auricle (Farkas et al;Ferrario et al, 1999;Brucker et al;Kalcioglu et al;Barut & Aktunc, 2006;Bozkir et al;Purkait & Singh, 2007) but studies investigating the asymmetry of auricle were very rare (Jung & Jung, 2003;Liu, 2008) and to our best knowledge there was only one study investigating the relation of auricle asymmetry and hand preference (Jung & Jung). The aims of this study were to determine various morphometric measurements of right and left auricles, to investigate asymmetry and its relation with handedness in both sexes.…”
Section: Introductionmentioning
confidence: 99%